PERAN MEDIA TERHADAP HUBUNGAN INDONESIA-MALAYSIA DALAM KASUS REOG, TARI PENDET DAN BATIK - Zulhamdi Yahmin (2013)
Diplomatic relations between Indonesia - Malaysia is very interesting to discuss because the two countries have a very volatile political climate when compared to bilateral relations with other countries ASEAN region. Indonesia and Malaysia are the countries that are geographically close, besides Indonesia and Malaysia also tend to have the same culture as the same set of historical. Massive migration of Indonesian society during colonialism has led to the existence of cultural cooperation betw